Indigenous women, globalization, food and social policies in the “Amazon Trapezoid” - Germán Alfonso Palacio; Juana Valentina Nieto (Mundo Amazónico, 2014)
This article is part of a broader research conducted during 2009-2010. It tries to understand the range of possibilities that the socio-political and natural environment offers to indigenous women to solve food problems in the Amazon Trapezoid in Colombia, particularly in Leticia. This research differentiates between urban and rural indigenous women, and tries to contribute to a broader research, offering a general framework to understand the significance and conditions imposed by globalization and public policies targeting indigenous women. It is an attempt to offer explanatory elements to understand mediations between the micro and the local vis-a-vis the state and the global scales. A source of social power for indigenous women in the Amazon is the “chagra”, a sort of women indigenous right to use the land to produce food and other land products. Some international institutions and state agencies have incorporated a gender perspective in their projects, assuming that women are more responsible and administer better family resources than men. However, other type of evident outcomes is that women are being socialized in dealing with money. This question arises: are these programs strengthening women indigenous power? Or are they preparing the road for a more commercial, capitalist economy in the Amazon?